MODEL DIGITAL MARKETING DALAM BISNIS RETAILER - Dewi Mariam Widianiarsih; Arum Arupi Kusnindar (Universitas Muhammadiyah Prof. DR. HAMKA, 2022)
The pandemic conditions with social restrictions have resulted in people not being able to buy and sell as they usually do. The ban on work, school and economic activities makes people have to stay at home and one of the bridges for them with the outside world is social media/internet. The phenomenon that can be observed during the pandemic is the emergence of retailers who use the internet as a marketing medium. Not only small retailers but also quite large retailers. At large retailers they are not only looking for end customers but also looking for distribution channels by opening up opportunities to become resellers. This phenomenon not only gave rise to many new entrepreneurs and business units but also gave rise to several new business models. New business models that emerge will affect the current market, established companies especially MSMEs must also be able to adapt to the transformations carried out from the strategy level to execution. This journal has a theoretical approach to the phenomenon of changing business models in the digital era and provides a conceptual framework for how the business model will affect the market and how the company's strategy.